2017
DOI: 10.1108/jiabr-03-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

A review of efficiency measures for REITS and their specific application for Malaysian Islamic REITS

Abstract: Purpose This paper aims to present a conceptual model on the efficiency of Islamic real estate investment trusts (I-REITs) available in Malaysia. The key difference between the Islamic and their conventional investment vehicle part is mainly its own Shariah framework. For instance, I-REITS must comply with the requirement of Securities Commission Act 1993 as well as the Guidelines on Islamic Real Estate Investment Trusts (Islamic REITs Guidelines). Design/methodology/approach The paper reviews and synthesise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Studies found that macroeconomic policy and variables have fundamental and long-run relationship with performance of REITs markets, with usually any shocks will tend to lower the REITs returns compared to investors' expectation. There is also a study by (Nazlioglu, Gormus, & Soytaş, 2016) (Chuweni & Ahmad, 2014;Chuweni & Eves, 2017;Mohamad & Saad, 2012;A. Osmadi & Razali, 2014;Teh, Soh, & Yan, 2012;Yahya et al, 2016;Zainuddin & Nordin, 2016), which is not surprising since the first I-REITs in the world, the Al 'Aqar KPJ REIT is based in Malaysia (Najeeb & Vejzagic, 2013).…”
Section: Reits Performance Risk and Volatilitymentioning
confidence: 96%
See 1 more Smart Citation
“…Studies found that macroeconomic policy and variables have fundamental and long-run relationship with performance of REITs markets, with usually any shocks will tend to lower the REITs returns compared to investors' expectation. There is also a study by (Nazlioglu, Gormus, & Soytaş, 2016) (Chuweni & Ahmad, 2014;Chuweni & Eves, 2017;Mohamad & Saad, 2012;A. Osmadi & Razali, 2014;Teh, Soh, & Yan, 2012;Yahya et al, 2016;Zainuddin & Nordin, 2016), which is not surprising since the first I-REITs in the world, the Al 'Aqar KPJ REIT is based in Malaysia (Najeeb & Vejzagic, 2013).…”
Section: Reits Performance Risk and Volatilitymentioning
confidence: 96%
“…Other studies have tried to find empirical evidence of I-REITs performance, most of them are cases of Malaysia (Akinsomi et al, 2016;Chuweni & Eves, 2017;Ma'in et al, 2016;Mohamad & Saad, 2012;A. Osmadi & Razali, 2014;Teh et al, 2012;Yahya et al, 2016).…”
Section: Reits Performance Risk and Volatilitymentioning
confidence: 99%
“…The performance of M-REITs are also measured using the non-parametric approach of data envelopment analysis in terms of efficiency and productivity performance (Chuweni and Eves, 2017, 2019; Chuweni et al , 2017; Chuweni et al , 2019; Chuweni et al , 2018). Islamic REITs exhibited higher efficiency and productivity performance as compared to their counterparts (Chuweni and Eves, 2019; Chuweni et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Chuweni (2018), the purpose of conventional performance measurement methods is to evaluate the return of investment by measuring risk of the REITs towards its returns with its insinuated benchmark. Chuweni and Eves (2017) provide a review of efficiency measures for REITs and their specification application for Malaysian Islamic REITs. In their study, the measures used among others are Markowitz’s (1952, 1959, 1991) mean variance portfolio theory, Sharpe’s (1966) ratio, Treynor’s (1965) ratio and Jensen’s (1968) alpha ratio with limited studies on the efficiency ratio of M-REITs particularly examining according to the type and property sectors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the efficient frontier analysis can capture the actual performance of an entity that is beyond the financial ratio analysis (Alsharif, 2020a). The financial ratio analysis also does not reflect the efficiency in utilizing the REITs' resources, and the efficient frontier analysis promotes competitiveness in the REITs industry as each REIT wants to lie on the efficient frontier (Chuweni and Eves, 2017). This paper contributes to the literature in various ways.…”
Section: Introductionmentioning
confidence: 99%